Comprehensive Analysis of the Health Level of BCA Syariah Bank Based on CAMELS Parameters Period 2019 – 2024 - Lusiana Febrianti; Ujang Syahrul (LP2M IAIN Palopo, 2026)
This study aims to analyze the financial health level of BCA Syariah Bank during the 2019-2024 period using the CAMELS approach, which includes aspects of Capital, Asset, Management, Earning, Liquidity, and Sensitivity to Market Risk. The method used is quantitative-descriptive with secondary data obtained from annual financial reports and OJK official publications. The analysis was conducted using the ratio assessment method and longitudinal trend measurement for six years. The results show that BCA Syariah is consistently in the healthy category. The Capital Adequacy Ratio (CAR) remains high despite a gradual decline, while the Non Performing Financing (NPF) ratio remains below the safe limit. Profitability indicators such as ROA and NIM showed an upward trend, accompanied by improved operational efficiency through a decrease in BOPO. The FDR ratio also stabilized within the optimal range, indicating good liquidity management. This study strengthens the CAMELS evaluation model in the context of Islamic banking and provides practical contributions for bank management and policy implications for regulators. This study also opens up room for further research with advanced quantitative approaches and broader objects.